2005
DOI: 10.1021/jf051116n
|View full text |Cite
|
Sign up to set email alerts
|

Red Chicories as Potent Scavengers of Highly Reactive Radicals:  A Study on Their Phenolic Composition and Peroxyl Radical Trapping Capacity and Efficiency

Abstract: Eight varieties of Cichorium genus vegetables (five heavily red colored, one red spotted, and two fully green) were investigated for their phenolic content (by HPLC and UV-vis spectrophotometry) and for their antioxidant activity. In particular, the capacity (that is, the amount of trapped peroxyl radicals) and the efficiency (that is, the amount of antioxidant necessary to halve the steady-state concentration of peroxyl radicals) were measured. All of the studied chicories are characterized by the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
59
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 25 publications
11
59
0
2
Order By: Relevance
“…Due to the presence of substantial amounts of polyphenols in the red chicories, a single serving of this vegetable (100 g) can contribute up to 400 mg total polyphenols to the human diet. These amounts represent a significant contribution to the daily intake of 1 g/day of polyphenols, as reported in the previous studies (Scalbert & Williamson 2000;Rossetto et al 2005).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Due to the presence of substantial amounts of polyphenols in the red chicories, a single serving of this vegetable (100 g) can contribute up to 400 mg total polyphenols to the human diet. These amounts represent a significant contribution to the daily intake of 1 g/day of polyphenols, as reported in the previous studies (Scalbert & Williamson 2000;Rossetto et al 2005).…”
Section: Discussionsupporting
confidence: 77%
“…Polyphenols are compounds that have high AOP, so the correlation between TPCs and AOPs is positive and statistically significant (r = 0.46). These levels of antioxidants in chicory can have important contributions to the recommended daily intake of antioxidants (Rossetto et al 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavones and flavonols are easier to identify than anthocyanins because they are more stable [21]. Several polyphenols, such as derivatives of hydroxycinnamic acids (HCA), flavonoids, and anthocyanins [4,6,[22][23][24][25][26][27], previously determined in radicchio leaves are presented in Table 1 Lipids are derived from long-chain fatty acids and alcohols or closely related derivatives. They are water-insoluble components of cells that can be extracted by nonpolar solvents.…”
Section: Introductionmentioning
confidence: 99%
“…D'Evoli et al [2] found cyanidin-3-O-(6''malonyl)-glucoside the predominant anthocyanin in Treviso Red Cichory. Studies carried out on the same ecotypes demonstrated that anthocyanins exerted a high peroxyl radical scavenging activity [3], furthermore D'Evoli et al [4] highlighted a direct scavenging effect against ROS formation in terms of antioxidant, cytoprotective activities and antiproliferative activity in Caco-2 cell exerted by the red part of the leaf compared with the whole leaf. Azzini et al [5] found beneficial effects of polyphenol-rich extracts from Treviso Red Cichory in counteracting the oxidative stress and cellular damage in in vitro Caco-2 cells model.…”
Section: Introductionmentioning
confidence: 97%